Adaptive burst assembly and intelligent offset time scheme for time-sensitive applications over optical burst switching networks - Abdulsalam Abdullah Mohammed Yayah; Abdul Samad Ismail, supervisors; Fakulti Kejuruteraan. Sekolah Komputeran 619086 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Doktor Falsafah (Sains Komputer)) - Universiti Teknologi Malaysia, 2017